A Knowledge Management System to Classify Social Educational Resources Within a Subject Using Teamwork Techniques - Séin-Echaluce, María Luisa; Fidalgo Blanco, Ángel; J. García-Peñalvo, Francisco; Conde, Miguel Ángel (Learning and Collaboration Technologies, 2015)
The traditional way to develop contents for a subject is based on the faculty perception and experience, however students should be taken into account. This work proposes a methodology that promotes the creation, classification and organization both teachers’ and students’ learning resources within the same subject scope in a timeless manner. Teamwork process is monitored by a proactive method that makes possible the generation of resources collaboratively. A knowledge management system allows to Classify, Search, Organize, Relate and Adapt the generated resources and includes a semantic search engine, based on ontologies, which provides a final product for users’ needs. A first iteration of an action-research allows answering questions such as the types of resources created during the teamwork (with academic, social and service orientation), how to stablish a common organization of the created knowledge for all potential users and improve educational resources of an academic subject with these collaborative resources.